The transfer of diatoms from freshwater to footwear materials: An experimental study assessing transfer, persistence, and extraction methods for forensic reconstruction. Issue 5 (September 2017) - Levin, E.A.; Morgan, R.M.; Scott, K.R.; Jones, V.J.
Abstract: In recent years there has been growing interest in environmental forms of trace evidence, and ecological trace evidence collected from footwear has proved valuable within casework. Simultaneously, there has been growing awareness of the need for empirical experimentation to underpin forensic inferences. Diatoms are unicellular algae, and each cell (or 'frustule') consists of two valves which are made of silica, a robust material that favours their preservation both in sediments and within forensic scenarios. A series of experiments were carried out to investigate the transfer and persistence of diatoms upon common footwear materials, a recipient surface that has historically been overlooked by studies of persistence. The effectiveness of two novel extraction techniques (jet rinsing, and heating and agitation with distilled water) was compared to the established extraction technique of hydrogen peroxide digestion, for a suite of five common footwear materials: canvas, leather, and 'suede' (representing upper materials), and rubber and polyurethane (representing sole materials). It was observed that the novel extraction technique of heating and agitation with distilled water did not extract fewer diatom valves, or cause increased fragmentation of valves, when compared to peroxide digestion, suggesting that the method may be viable where potentially hazardous chemical reactions may be encountered with the peroxide digestion method. Valves could be extracted from all five footwear materials after 3 min of immersion, and more valves were extracted from the rougher, woven upper materials than the smoother sole materials. Canvas yielded the most valves (a mean of 2511/cm 2 ) and polyurethane the fewest (a mean of 15/cm 2 ). The persistence of diatoms on the three upper materials was addressed with a preliminary pilot investigation, with ten intervals sampled between 0 and 168 h. Valves were seen to persist in detectable quantities after 168 h on all three upper materials. However, some samples produced slides with no valves, and the earliest time after which no diatom valves were found was 4 h after the transfer. Analysis of the particle size distributions over time, by image analysis, suggests that the retention of diatoms may be size-selective; after 168 h, no particles larger than 200 μm 2 could be found on the samples of canvas, and > 95% of the particles on the samples of suede were less than or equal to 200 μm 2 . A pilot investigation into the effects of immersion interval was carried out upon samples of canvas. Greater numbers of valves were extracted from the samples with longer immersion intervals, but even after 30 s, > 500 valves could be recovered per cm 2, suggesting that footwear may be sampled for diatoms even if the contact with a water body may have been brief. These findings indicate that, if the variability within and between experimental runs can be addressed, there is significant potential for diatoms to be incorporated into the trace analysis of footwear and assist forensic reconstructions. Highlights: Diatoms transfer to footwear materials after even short periods of immersion. Diatoms could be recovered from canvas, leather, and suede after 168 h (7 days). A novel extraction technique extracted similar numbers of valves to the established H2 O2 method. The novel extraction method did not cause higher levels of fragmentation. Larger diatoms appeared to persist over shorter timescales.